Perceived burden and quality of life in Chinese caregivers of people with serious mental illness: A path analysis - Zeng, Yingchun (International Journal of Psychosocial Rehabilitation, 2016)
Perceived burden and quality of life in Chinese caregivers of people with serious mental illness: A path analysis